1999
DOI: 10.1016/s0014-5793(99)01546-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression of mammalian SPO11/TOP6A homologs during meiosis1

Abstract: As the initiator of DNA double-strand breaks during meiosis in Saccharomyces cerevisiae, the SPO11 protein is essential for recombination. Similarity between SPO11 and archaebacterial TOP6A proteins points to evolutionary specialization of a DNA cleavage function for meiotic recombination. To determine whether this extends to mammals, we isolated and characterized mouse and human SPO11 cDNAs. Mammalian SPO11 genes were found to be expressed at high levels only in testis, wherein mouse Spo11 transcript is restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
(37 reference statements)
3
29
2
Order By: Relevance
“…some (40). As a control, SPO11 was expressed at postnatal day 12, consistent with a previous report (41).…”
Section: Localization and Characterization Of Plb In Murine Sperm-supporting
confidence: 91%
“…some (40). As a control, SPO11 was expressed at postnatal day 12, consistent with a previous report (41).…”
Section: Localization and Characterization Of Plb In Murine Sperm-supporting
confidence: 91%
“…This result is in apparent contrast with the expression pattern and activity of Spo11 gene, which was found in all the stages of the meiotic prophase up to pachytene cells (Baudat et al, 2000;Romanienko and Camerini-Otero, 2000;Shannon et al, 1999). This discrepancy can be explained by a difference in the timing of Cre translation with respect to Spo11, and/or by a Cre recombinase activity below the threshold detectable by -gal staining at the beginning of male meiosis, arguing for the requirement of an accumulation of Cre to efficiently delete loxP sites.…”
Section: Generation Of Spo11-ires-cre Mice and Cre Expressioncontrasting
confidence: 61%
“…Molecular and genetic studies in other fungi and higher eukaryotes have demonstrated that Spo11 orthologs are universally required for the initiation of meiotic recombination. Furthermore, Schizosaccharomyces pombe (Lin and Smith 1994), Drosophila melanogaster (McKim and Hayashi-Hagihara 1998), Caenorhabditis elegans (Dernburg et al 1998), Arabidopsis thaliana (Grelon et al 2001), Coprinus cinereus (Celerin et al 2000), Sordaria macrospora , Mus musculus (Baudat et al 2000;Metzler-Guillemain and de Massy 2000;Romanienko and Camerini-Otero 2000) and also Homo sapiens (Romanienko and Camerini-Otero 1999;Shannon et al 1999) maintain and require Spo11 orthologs.…”
mentioning
confidence: 99%